2006
DOI: 10.1074/jbc.m509421200
|View full text |Cite
|
Sign up to set email alerts
|

Study of Highly Constitutively Active Mutants Suggests How cAMP Activates cAMP Receptor Protein

Abstract: and Ser 128 and (ii) the concomitant reorientation of the ␤4/␤5 loop. Finally, we also report that elevated expression of T127L/S128I CRP markedly perturbed E. coli growth even in the absence of cAMP, which suggests why comparably active variants have not been described previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
63
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 44 publications
3
63
0
Order By: Relevance
“…This aberrant gene expression may be the cause of the growth impairment observed on minimal media with the class II mutants. Interestingly, a similar phenomenon has been observed for Escherichia coli, where highly constitutive mutants of the cAMP activator protein have been shown to inhibit cell growth (51). Nonetheless, the growth phenotype of the class II mutants is puzzling in that strains containing a null mutation in glnA, the gene encoding GS, are able to grow on glutamine minimal media even though TnrA is constitutively active (45).…”
Section: Vol 189 2007mentioning
confidence: 77%
“…This aberrant gene expression may be the cause of the growth impairment observed on minimal media with the class II mutants. Interestingly, a similar phenomenon has been observed for Escherichia coli, where highly constitutive mutants of the cAMP activator protein have been shown to inhibit cell growth (51). Nonetheless, the growth phenotype of the class II mutants is puzzling in that strains containing a null mutation in glnA, the gene encoding GS, are able to grow on glutamine minimal media even though TnrA is constitutively active (45).…”
Section: Vol 189 2007mentioning
confidence: 77%
“…CRP is a homodimer in which each subunit contains two domains, the cAMP-binding domain and the DNA-binding domain, separated by a hinge region (27). The structure of the inactive form of CRP has never been determined, so the mechanism of allosteric activation by cAMP is conjectural, but plausible models for the conformational change that cAMP effects have been proposed (29,39).…”
mentioning
confidence: 99%
“…CRP is a homodimer in which each subunit contains two domains, the cAMP-binding domain and the DNA-binding domain, separated by a hinge region (27). The structure of the inactive form of CRP has never been determined, so the mechanism of allosteric activation by cAMP is conjectural, but plausible models for the conformational change that cAMP effects have been proposed (29,39).CRP variants have been found that have altered ligand specificity (1,5,9,14,19,23,40). The substitutions in some of these variants lie in the effector-binding pocket itself and presumably alter the specific interactions between CRP and the ligand (23, 40).…”
mentioning
confidence: 99%
See 2 more Smart Citations